Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 9 - Cumulative Review: 27

Answer

a. $x(2x+7)(2x-7)$ b. $2(9x^2+1)(3x+1)(3x-1)$

Work Step by Step

a. $4x^3-49x$ $=x(4x^2-49)$ $=x(2x+7)(2x-7)$ b. $162x^4-2$ $=2(81x^4-1)$ $=2(9x^2+1)(9x^2-1)$ $=2(9x^2+1)(3x+1)(3x-1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.